2010
DOI: 10.1348/000709910x497130
|View full text |Cite
|
Sign up to set email alerts
|

Example‐based learning: Effects of model expertise in relation to student expertise

Abstract: This study suggests that when worked examples are based on actual performance, rather than an ideal procedure, expert models are to be preferred over advanced student models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
5
35
0
Order By: Relevance
“…Additionally, learning sciences research has shown that novices learn more from their peers than from experts when being trained directly on the task they are tested on [11]. However, expert examples have been shown to be more effective than peer examples on transfer tasks-tasks that share some, but not all, properties of the examples [11,4,16]. As each of our complex web search queries are quite different from one another, we expect our tasks to be in the transfer regime.…”
Section: Learning Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, learning sciences research has shown that novices learn more from their peers than from experts when being trained directly on the task they are tested on [11]. However, expert examples have been shown to be more effective than peer examples on transfer tasks-tasks that share some, but not all, properties of the examples [11,4,16]. As each of our complex web search queries are quite different from one another, we expect our tasks to be in the transfer regime.…”
Section: Learning Sciencesmentioning
confidence: 99%
“…This can be seen as an analogue to the worked example effect, but instead of simply reading through an example, the worker must read and validate the work of a peer worker. However, the learning sciences literature suggests that expert examples are more effective than peer examples for transfer tasks [11,4,16]. These findings suggest the following hypothesis:…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, research focusing on expertise in the field of physiotherapy is narrow (Boekhout et al, 2010;Piirainen and Viitanen, 2010). Some studies have focused on how physiotherapy students acquire regulative knowledge, such as reflective and critical thinking skills, in practice (Bartlett and Cox, 2002;Clouder and Toms, 2008;Cole and Wessel, 2008;Donaghy and Morss, 2007;Roche and Coote, 2008), whereas only Le Maistre and Parè (2006) have attempted to present a holistic model of expert knowledge in the field of physiotherapy.…”
Section: How Skill Has Been Conceptualizedmentioning
confidence: 99%
“…This example-based method, referred to as a worked example, has proven effective consistently as an instructional intervention in the study of problem solving. 20 A worked example, in its simplest form, is defined as a procedure for solving a problem with one correct answer, and it has long been associated with the teaching of solutions to problems in domains such as algebra, physics, and computer programming. Zhu and Simon substituted worked examples for lectures and other classroom activities in physics problem-solving among college students with promising results in knowledge acquisition.…”
Section: Literature Reviewmentioning
confidence: 99%